The Effect of Managerial Ownership and Capital Structure on Stock Returns With Dividend Policy As an Intervening Variable - R. Dian Wirdiansyah; Agus Munandar (Publikasi Indonesia, 2023)
The purpose of this study is to obtain empirical evidence for the impact of manager ownership and capital structure on stock returns, mediated by dividend policy. Manager ownership is tested by comparing the size of shares owned by the manager to the total number of shares. The size of the capital structure is tested by the leverage ratio, which represents the company's total debt to equity. A stock's return is measured by comparing the market price at the beginning of the year to the market price at the end of the year. The study population utilizes the consumer goods industry listed on the Indonesian Stock Exchange in 2020-2021 consumer goods industry. A sample of 25 companies was extracted based on the target sampling method. This study proves that management ownership and capital structure influence dividend policy. Management ownership and dividend policy affect stock returns, but capital structure does not. Furthermore, the results of the Sobel test prove that dividend policy does not convey the impact of management ownership and capital structure on stock returns.